Acesso remoto em firewalls e topologia para gateways VPN - Figueiredo, Francisco José Candeias; Geus, Paulo Lício de (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2001: Anais do I Workshop em Segurança de Sistemas ComputacionaisDO - 10.5753/sbseg.2001.21292, 2001)
VPNs are being hailed as the solution for several situations involved in the Internet these days. Firewalls have seen a decade of evolution and sophistication to deal with specific problems. However, we are also seeing the proliferation of VPN configurations on otherwise secure networks based on firewalls. This paper discusses the security problems incurred by the adoption of VPN gateways in standard firewalls. It also suggests more secure topology solutions for the standard VPN uses, as well as for the remote access client. We also propose an implementation based on freely available software that satisfies the security issues brought about by this paper.